2021
DOI: 10.1111/ropr.12442
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for five electricity grid decarbonization policies in California

Abstract: The climate crisis and associated push for distributed, renewable electricity generation necessitate policy changes to decarbonize and modernize the electricity grid. Some of these changes—e.g., smart meter rollouts and tax credits for solar panel adoption—have received attention in the media and from social scientists to understand public perceptions and responses. Others—e.g., allowing peer‐to‐peer electricity sales, promoting residential electrification, requiring solar panels on new development, funding mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…As the predominance of electricity comes from hydroelectric plants, periods of drought can justify possible fluctuations in its production, which reinforces the country's need to diversify its production by investing in other renewable sources. Besides that, as the climate in the region is dependent on a series of conditions such as atmospheric pressure, air temperature, and humidity [47], solar power, for instance, can be affected by cloudiness and other factors [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Nonetheless, despite the concern with climate change issues, there have been efforts towards diversifying the sources of renewable energy [49].…”
Section: Analysis and Discussion Of G20 Contributions To Renewable El...mentioning
confidence: 99%
See 1 more Smart Citation
“…As the predominance of electricity comes from hydroelectric plants, periods of drought can justify possible fluctuations in its production, which reinforces the country's need to diversify its production by investing in other renewable sources. Besides that, as the climate in the region is dependent on a series of conditions such as atmospheric pressure, air temperature, and humidity [47], solar power, for instance, can be affected by cloudiness and other factors [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Nonetheless, despite the concern with climate change issues, there have been efforts towards diversifying the sources of renewable energy [49].…”
Section: Analysis and Discussion Of G20 Contributions To Renewable El...mentioning
confidence: 99%
“…Denmark, for instance, has achieved remarkable success in renewable energy development over the last several decades, since the country mostly depends on wind energy [38], with 48% of its energy mix being from wind, [39]. Moreover, in the US, California is a state recognized for its innovative energy policy, mainly for the adoption of large amounts of solar panels in recent years [40]. Also in the US, [41] used life cycle assessment and revealed that deployment of renewable electricity generation devices to off-grid remote locations for electricity generation can have the same, or less, environmental impact as urban grid systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As smart meters become more ubiquitous in households across the world, new advances are needed to efficiently process the deluge of data streams produced from these devices and then generate actionable insights-especially in a way that has low computational overhead and does not require continuous human-in-the loop interactions [11]. In particular, using smart meter data to understand household level energy use is an ongoing challenge, and with it comes the difficulties in developing meaningful interventions that can ease burdens on the grid while maintaining customer engagement and satisfaction [12]. For example, one such motivation for household-level energy interventions is to reduce greenhouse gas emissions from nonrenewable generation sources (e.g., natural gas "peaker" power plants) during periods of high demand, while also expanding the potential for customers to change their energy behaviors and appliance purchases to save money on their energy bills [13].…”
Section: Introductionmentioning
confidence: 99%